Young women’s risk of sexual aggression in bars: The roles of intoxication and peer social status - Graham, Kathryn; Bernards, S.; Abbey, A.; Dumas, T.; Wells, S. (Wiley-Blackwell Publishing Ltd., 2014)
Introduction and Aims: Previous research suggests a link between women's drinking and sexual victimisation; however, little is known about other factors that influence risk and how risks are linked to drinking-in-the-event. We examined how amount of alcohol consumed and peer group factors were associated with whether young women were targeted for sexual aggression on a night out at a bar. Design and Methods: One hundred and fourteen women recruited in small groups in the bar district reported how many drinks they had consumed and were breath-tested at recruitment and on their way home. At recruitment, they also ranked other members of their group in terms of status (e.g. popularity, group influence). In the exit survey, they reported any sexual aggression they experienced that night (i.e. persistence after refusal and unwanted sexual touching). Results: Over a quarter (28.9%) of women reported persistence only, 5.3% unwanted touching only and 18.7% both. Sexual aggression was associated with consuming more alcohol on the survey night and whether other group members experienced sexual aggression that night. The relationship with amount consumed was stronger for touching than for persistence. Having a lower status position in the group was associated with increased risk of sexual aggression among women who had consumed five or more drinks. Discussion and Conclusions: Prevention should address social norms and other factors that encourage men to target specific women for sexual aggression, including perceptions by staff and patrons that intoxicated women are ‘easy’ or more blameworthy targets and the possible role of women's social status in their peer groups.